Evaluation of chemopreventive effects of Acanthus ilicifolius against azoxymethane-induced aberrant Crypt Foci in the rat colon. - Amel A Almagrami; Mohammed A Alshawsh; Riyadh Saif-Ali; Abdrabuh Shwter; Sameer D Salem; Mahmood A Abdulla (PLoS ONE, 2014)
BACKGROUND: Acanthus ilicifolius, a mangrove medicinal plant, is traditionally used to treat a variety of diseases. The aim of this research is to assess the chemoprotective outcomes of A. ilicifolius ethanolic extract against azoxymethane (AOM) induced colonic aberrant crypt foci (ACF) in rats. METHODOLOGY/PRINCIPAL FINDINGS: In our study, rats were arranged in to five groups. Rats in the normal control group were given subcutaneous injections of normal saline once weekly for 2 weeks. The AOM control, reference and treatment groups were given subcutaneous injection of AOM, 15 mg/kg body weight, once weekly for 2 weeks each. The reference group was treated with 35 mg/kg 5-Fluorouracil via intraperitoneal injection once weekly for 8 weeks, and the treatment groups were administered by gavage with 250 and 500 mg/kg A. ilicifolius extract daily for 8 weeks. Both normal and AOM control groups received the vehicle; 10% Tween-20 only. Rats treated with 250 mg/kg and 500 mg/kg of A. ilicifolius extracts showed a decrease in the mean number of ACF by 65% and 53%, respectively. Those fed with A. ilicifolius showed significantly decreased multiplicity of ACF formations when compared with the results from the AOM control group. The 250 mg/kg A. ilicifolius treatment group showed significant decreases in lipid peroxidation MDA levels when compared with the AOM control group. In immunohistochemistry staining, the proliferating nuclear cell antigen (PCNA)-positive cells were significantly higher in the AOM control group than in the A. ilicifolius-treated groups. RT-PCR showed that A. ilicifolius caused a change in the regulation of apoptosis-related genes expression. CONCLUSION/SIGNIFICANCE: The results of the current study show that AOM-treated rats receiving oral exposure to A. ilicifolius demonstrated a significant decrease in the number of ACF in the colon when compared to AOM-treated rats receiving vehicle only. A ilicifolius may be an effective herbal approach for the prevention of AOM-induced ACF in the rat colon.